VD_FINDINFO HC / 2014 / 491 vom 25. Juni 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, RÉSILIATION ABUSIVE, DÉLAI DE GARDE, OBSERVATION DU DÉLAI | 257d al. 2 CO, 271 al. 1 CO, 257 CPC (CH)